At-risk studies and clinical antecedents of psychosis, bipolar disorder and depression: a scoping review in the context of clinical staging. Issue 2 (4th June 2018) - Hartmann, Jessica A; Nelson, Barnaby; Ratheesh, Aswin; Treen, Devi; McGorry, Patrick D
Abstract: Identifying young people at risk of developing serious mental illness and identifying predictors of onset of illness has been a focus of psychiatric prediction research, particularly in the field of psychosis. Work in this area has facilitated the adoption of the clinical staging model of early clinical phenotypes, ranging from at-risk mental states to chronic and severe mental illness. It has been a topic of debate if these staging models should be conceptualised as disorder-specific or transdiagnostic. In order to inform this debate and facilitate cross-diagnostic discourse, the present scoping review provides a broad overview of the body of literature of (a) longitudinal at-risk approaches and (b) identified antecedents of (homotypic) illness progression across three major mental disorders [psychosis, bipolar disorder (BD) and depression], and places these in the context of clinical staging. Stage 0 at-risk conceptualisations (i.e. familial high-risk approaches) were identified in all three disorders. However, formalised stage 1b conceptualisations (i.e. ultra-high-risk approaches) were only present in psychosis and marginally in BD. The presence of non-specific and overlapping antecedents in the three disorders may support a general staging model, at least in the early stages of severe psychotic or mood disorders.